Recognizing the importance of unmanaged forests to mitigate climate change. Issue 12 (27th July 2020) - Kun, Zoltán; DellaSala, Dominick; Keith, Heather; Kormos, Cyril; Mercer, Bernard; Moomaw, William R.; Wiezik, Michal
Abstract : The carbon stock in Europe's forests is decreasing and the importance of protecting 'unmanaged' forests must be recognised in reversing this process. In order to keep carbon out of the atmosphere and to meet the Paris Agreement goals, the remaining primary forests must be protected and secondary forests should be allowed to continue growing to preserve existing carbon stocks and accumulate additional stocks. Scientific evidence suggests that 'unmanaged' forests have higher total biomass carbon stock than secondary forests being actively managed for commodity production or recently abandoned.